A facile route to homogeneous high density networks of metal nanoparticles - Charrault, Eric (Langmuir : the ACS journal of surfaces and colloids, 2009)
In this communication, we report an inexpensive and simple-to-implement method using self-assembly properties of surfactants onto solid substrates for patterning square centimeter surfaces with a high density of catalyst metal nanoparticles with narrow size distributions. This method, which uses patterns of hemimicelles of partially fluorinated alkanes as masks and over metal evaporation, leads to typical particle sizes and spacings of 2 and 25 nm, respectively, arranged in a hexagonal network with a density of about 10(11) particles/cm2. Using gold as the metal, we show the ability of such material to catalyze the oxidation reaction of carbon monoxide into carbon dioxide at low temperature